2017
DOI: 10.1016/j.neurobiolaging.2017.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide piRNA profiling in human brains of Alzheimer's disease

Abstract: Discovered in the brains of multiple animal species, piRNAs may contribute to the pathogenesis of neuropsychiatric illnesses. The present study aimed to identify brain piRNAs across transcriptome that are associated with Alzheimer’s disease (AD). Prefrontal cortical tissues of six AD cases and six controls were examined for piRNA expression levels using an Arraystar HG19 piRNA array (containing 23,677 piRNAs) and genotyped for 17 genome-wide significant and replicated risk SNPs. We examined whether piRNAs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 57 publications
0
58
0
Order By: Relevance
“…Recent evidence suggests that piRNAs are abundant in the brain (Mani and Juliano 2013; Rajasethupathy et al 2012; Lee et al 2011; Sharma et al 2001; Perrat et al 2013; Yan et al 2011; Ghildiyal et al 2008; Dharap et al 2011; Peng and Lin 2013; Zuo et al 2016b; Qiu et al 2017). piRNAs may regulate the mRNAs and translation of the proximate risk genes (Grivna et al 2006) or interact with neurotransmitters in brains (Ross et al 2014; Rajasethupathy et al 2012), and thus may play roles in brain disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence suggests that piRNAs are abundant in the brain (Mani and Juliano 2013; Rajasethupathy et al 2012; Lee et al 2011; Sharma et al 2001; Perrat et al 2013; Yan et al 2011; Ghildiyal et al 2008; Dharap et al 2011; Peng and Lin 2013; Zuo et al 2016b; Qiu et al 2017). piRNAs may regulate the mRNAs and translation of the proximate risk genes (Grivna et al 2006) or interact with neurotransmitters in brains (Ross et al 2014; Rajasethupathy et al 2012), and thus may play roles in brain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…These risk SNPs were genotyped in our own small cohort (6 AD and 6 controls) to replicate the SNP-AD association (Qiu et al 2017), which was approved by the ethics committee of The Institute of Basic Medical Sciences of the Chinese Academy of Medical Sciences.…”
Section: Summary Of Materials and Methods (Much Detailed In The Sumentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a total of 9453 piRNAs were identified in human brains with 103 piRNAs showed altered expression in AD cases versus controls. What is more, most of the 103 piRNAs correlate with genome-wide significant risk SNPs indicating that piRNAs would be promising risk biomarkers of AD [79]. Interestingly, one research of the piRNAome on transient focal ischemia suggested that a total of 105 piRNAs showed differential expression in ischemic rat brain, although the function for the changes in those piRNA expressions still remains elusive, it was predicted that the role of altered piRNAome is to control mutagenesis through suppressing the aberrant transposon activity in the ischemic brain [80].…”
Section: Pirnas In Other Types Of Diseasesmentioning
confidence: 99%
“…These findings also suggest that piRNAs are a shared feature of this non-aging biological system, cancers. In an earlier work, we reported associations between piRNAs and Alzheimer's disease ( 26 ), a clinical condition strongly related to aging. Cancers are just opposite to the aging diseases in renewal and proliferation capacity, which also suggests a potential role of piRNAs in cancers.…”
Section: Introductionmentioning
confidence: 97%